2020
DOI: 10.26803/ijlter.19.10.4
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Natural Science Pre-Service Teachers during Work-Integrated Learning: A Case of a Lesson Study Approach

Abstract: This paper is concerned with the issue associated with final-year Natural Science pre-service teachers’ lesson design abilities. This paper reports how the implementation of a lesson study approach served as an intervention to support the lesson preparation abilities of pre-service teachers during a work-integrated learning (WIL) process. The case study generated rich qualitative data from multiple sources such as e-mail communications, WhatsApp responses, video capturing, and focus group team discussions. Cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…Epistemic success is the "collaborative knowledge-building, reflective learning, individual construction of knowledge and the ability to apply knowledge in practical situations" (Themane & Mabasa, 2021: 21). Botes, Moreeng and Mosia (2022) write about academic-literacy support interventions to supplement students' academic-literacy skill development. These authors also mention specialised cross-aged mentor support, which intends to aid with the academic needs of students who experience learning difficulties.…”
Section: Lareymentioning
confidence: 99%
“…Epistemic success is the "collaborative knowledge-building, reflective learning, individual construction of knowledge and the ability to apply knowledge in practical situations" (Themane & Mabasa, 2021: 21). Botes, Moreeng and Mosia (2022) write about academic-literacy support interventions to supplement students' academic-literacy skill development. These authors also mention specialised cross-aged mentor support, which intends to aid with the academic needs of students who experience learning difficulties.…”
Section: Lareymentioning
confidence: 99%
“…Empirical evidence has shown that the main difficulties concerning the operationalisation of an inclusive school culture have referred, in recent years, to the adequate training and preparation of the teacher and preservice teachers, both for the common class and for specialists (Watkins, 2012;European Agency for Special Needs and Inclusive Education, 2014;Ibe-Unesco, 2016;Simón et al, 2018;Botes et al, 2020), the need for changes in pedagogical practices (Aas, 2020;Holmqvist, 2020;Norwich et al, 2021), and, consequently, the educational process, which generally has sought to focus on students with different disabilities and special needs, rather than explore their full potential (Florian, 2019;Aas, 2020;Schlünzen et al, 2020). In addition, there is a body of research demonstrating that barriers to inclusion also include the lack of adaptation in the physical and architectural structure of the environment and accessibility in different aspects, especially the technological one (Almaiah et al, 2020;Beaunoyer et al, 2020;Dhawan, 2020;Leifler, 2020;Kim et al, 2021), and school leaders´ lack of knowledge about how to implement the aspects included in public policies (Schlünzen et al, 2020).…”
Section: Inclusive Education and The Ccm Approachmentioning
confidence: 99%
“…The study on how to train science teachers in South African by Wiets B. et al (2020) gives a recommendation on organizing a lesson study for pre-service teachers during the training process. In this study, the generation of knowledge was inseparably associated with the collaborative practices and interaction that existed between the team of pre-service teachers.…”
Section: Literature Reviewmentioning
confidence: 99%